PENGARUH KEPERCAYAAN, KEMUDAHAN, KUALITAS INFORMASI DAN PERSEPSI HARGA TERHADAP PEMILIHAN MODEL JASA TRANSPORTASI ONLINE (Studi Pada Pengguna Jasa Transportasi Online GrabCar) - Listyan Nur Fauziah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at determining the influence of trust, ease,quality of information and price perception on consumer’s decisions to selection online transport service model study on users of GrabCar online transportation services. This explanatory research explains the causal relationship between the variables through hypothesis testing. This study uses a sample of 120 respondents taken from the population of GrabCar (an online transportation service) users, which were selected using purposive sampling technique. The criteria of the respondents are people who are at least 18 years old and have used GrabCar's service. The data were analyzed using multiple linear regression. The results of subsequent analysis prove that trust, ease, information quality and price perception have a positive effect on consumer’s selection to uses GrabCar’s service, with the ease of having the greatest influence in the selection of GrabCar's online transport service model.Keywords: Trust, ease, quality of information, price perceptions, selection to use GrabCar's service model.